The impact of the development of science and technology on the fade of mankind - T. Jacob T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
The article discusses the participation of women in science and technology, and more extensive ly in medicine. It reiterates the nature of science and technology, and explains why science cannot be absolutely objective. Furthermore, it stresses on the increasing speed in the advancement of science and its influence, both positive and negative, on man at different levels of the living systems. In addition, the article probes the menace of the cult of technology and the dangers of the dynamic autonomy of science, especially the application of basic sciences in war efforts, the information revolution and the new biology which would affect life itself, the dignity of man. and even his very existence. Several ways out are suggested in confronting the negative impact of science and technology, such as adopting a new paradigm, the strengthening of scientific ethics, the protection of the consumers, and the rehumanization of science and technology. Key Words: science and technology - women's studies - futuristics - thought style - scientific ethics